The oceans are changing: impact of ocean warming and acidification on biofouling communities. Issue 5 (28th May 2019) - Dobretsov, Sergey; Coutinho, Ricardo; Rittschof, Daniel; Salta, Maria; Ragazzola, Federica; Hellio, Claire
Abstract: Climate change (CC) is driving modification of the chemical and physical properties of estuaries and oceans with profound consequences for species and ecosystems. Numerous studies investigate CC effects from species to ecosystem levels, but little is known of the impacts on biofilm communities and on bioactive molecules such as cues, adhesives and enzymes. CC is induced by anthropogenic activity increasing greenhouse emissions leading to rises in air and water temperatures, ocean acidification, sea level rise and changes in ocean gyres and rainfall patterns. These environmental changes are resulting in alterations within marine communities and changes in species ranges and composition. This review provides insights and synthesis of knowledge about the effect of elevated temperature and ocean acidification on microfouling communities and bioactive molecules. The existing studies suggest that CC will impact production of bioactive compounds as well as the growth and composition of biofouling communities. Undoubtedly, with CC fouling management will became an even greater challenge.